The hidden impact: the rate of nicotine metabolism and kidney health - Wang, Xiaona; Su, Shanshan (Frontiers in Endocrinology, 2024)
Abstract Objectives: The effects of nicotine metabolism on the kidneys of healthy individuals have not been determined. The nicotine metabolite ratio (NMR) indicates the rate of nicotine metabolism and is linked to smoking behaviors and responses to tobacco treatments.We conducted this study in order to investigated the relationship between nicotine metabolite ratio (NMR) and kidney function. Methods: An analysis of cross-sectional data of adults was conducted using a population survey dataset (National Health and Nutrition Examination Survey Data 2013/2018 of the United States). A weighted multivariate regression analysis was conducted to estimate the correlation between NMR and kidney function. Furthermore, we apply fitting smooth curves to make the relationship between NMR and estimated glomerular filtration rate (eGFR) more visualized. Results: The research included a total of 16153 participants. Weighted multivariate regression analyses adjusted for possible variables showed a negative relationship between NMR and estimated glomerular filtration rate (eGFR) .The β (95%CI) of the regression equation between NMR and eGFR was -2.24 (-2.92, -1.55), the trend testing showed consistent results. NMR is positively correlated with urinary albumin creatinine ratio (uACR), but it is not statistically significant. A stratified analysis found a negative correlation between NMR and eGFR in all age, gender and diabetes subgroups, the results were not statistically significant among Mexican Americans and other races. Notably, each unit rise in NMR corresponded to a 4.54 ml/min·1.73m² lower eGFR in diabetic participants and a 6.04 ml/min·1.73m² lower eGFR in those aged 60 and above. Conclusions: Our study shows that nicotine metabolite ratio is negatively associated with kidney function among most adults. It will be necessary to conduct more well-designed prospective clinical trials in order to determine the exact causal interactions between NMR and kidney function. Specific mechanisms also need to be further explored in basic experiments.